EAST alternative magnetic configurations: modelling and first experiments. (30th June 2015) - Calabrò, G.; Xiao, B.J.; Chen, S.L.; Duan, Y.M.; Guo, Y.; Li, J.G.; Liu, L.; Luo, Z.P.; Wang, L.; Xu, J.; Zhang, B.; Albanese, R.; et al.
Abstract: Heat and particle loads on the plasma facing components are among the most challenging issues to be solved for a reactor design. Alternative magnetic configurations may enable tokamak operation with a lower peak heat load than a standard single null (SN) divertor. This papers reports on the creation and control of one of such alternatives: a two-null nearby divertor configuration. An important element of this study is that this two-null divertor was produced on a large superconducting tokamak as an experimental advanced superconducting tokamak. A preliminary experiment with the second null forming a configuration with significant distance between the two nulls and a contracting geometry near the target plates was performed in 2014. These configurations have been designed using the FIXFREE code and optimized with CREATE-NL tools and are discussed in the paper. Predictive edge simulations using the TECXY code are also presented by comparing the advanced divertor and SN configuration. Finally, the experimental results of ohmic and low confinement (L-mode) two-null divertor and SN discharges and interpretative two-dimensional edge simulations are discussed. Future experiments will be devoted to varying the distance between the two nulls in high confinement (H-mode) discharges.